The Choice! The challenges of trying to improve medical students’ satisfaction with their specialty choices (Canadian Medical Education Journal, 2023)
The authors describe the residency match as a two-step process. The first step, the Choice, is where students use a combination of intuitive and analytic information processing to select the specialty that they believe will provide fulfilment and work-life balance over their entire career. The second step, the Match, uses a “deferred-acceptance” algorithm to optimize pairing of students and their specialty choices. Despite being the rate-limiting step, in the minds of students and other stakeholders, the outcomes of the Choice have typically been eclipsed by the outcomes of the Match. A recently published study found that during their second year of residency training, one in 14 physicians reported specialty choice regret, which associates with symptoms of burnout in residents. While the obvious solution is to design interventions that improve the specialty choices of students, this approach faces significant challenges, including the fact that: 1) satisfaction with specialty choice is a difficult-to-define construct; 2) specialty choice regret may be misattributed to a poor choice; and 3) choosing is a more complicated process than matching. The authors end by suggesting that if we hope to improve satisfaction with specialty choice then we should begin by defining this, deciding when to assess it, and then creating assessment tools for which there is validity evidence and that can identify the underlying causes of specialty choice regret.